2019
DOI: 10.1038/s41598-019-53819-6
|View full text |Cite
|
Sign up to set email alerts
|

Target Strength and swimbladder morphology of Mueller’s pearlside (Maurolicus muelleri)

Abstract: In the last few years, there has been increasing interest in the commercial exploitation of mesopelagic fish and a trawl-acoustic methodology has been recommended to make estimates of abundance of these resources. This study provides relevant information on the scattering properties of a key mesopelagic fish species in the Bay of Biscay, Mueller’s pearlside (Maurolicus muelleri), necessary to convert the acoustic density into numerical abundance. The target strength (TS) of pearlside was estimated for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 67 publications
2
25
0
1
Order By: Relevance
“…Also, it has been demonstrated that eDNA shedding rates are influenced by diet, feeding activity -being up to 10-fold times higher in fed fishes than in starving ones-and lifecycle stage of the individuals (Klymus et al 2015;Hansen et al 2018). Thus, the noticeable high relative abundance of M. muelleri DNA at epipelagic depths during night may not only indicate a higher biomass but also elevated feeding activity, in line with the existing ecological knowledge on this species; M. muelleri is a very abundant myctophid in the Bay of Biscay, well-known to perform DVM in big, compact schools to feed close to the surface after the sunset (Sobradillo et al 2019).…”
Section: Edna Can Infer Fish Diel Vertical Migratory Behaviorsupporting
confidence: 58%
“…Also, it has been demonstrated that eDNA shedding rates are influenced by diet, feeding activity -being up to 10-fold times higher in fed fishes than in starving ones-and lifecycle stage of the individuals (Klymus et al 2015;Hansen et al 2018). Thus, the noticeable high relative abundance of M. muelleri DNA at epipelagic depths during night may not only indicate a higher biomass but also elevated feeding activity, in line with the existing ecological knowledge on this species; M. muelleri is a very abundant myctophid in the Bay of Biscay, well-known to perform DVM in big, compact schools to feed close to the surface after the sunset (Sobradillo et al 2019).…”
Section: Edna Can Infer Fish Diel Vertical Migratory Behaviorsupporting
confidence: 58%
“…Orestias demersal behavior challenges the acoustic assessments, as Orestias can hide among submerged macrophytes [22] so our acoustics assessment may have been underestimated. However, the choice of the threshold (-68 dB) to observe small fish was based on Love's equation [46], which is successfully used in freshwater ecosystems [39,[43][44][45]54].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Previous studies suggested the mesopelagic community in the area was dominated by pearlside (Maurolicus inventionis) a small swimbladdered fish of the Sternoptychidae family (Kalinowski and Linkowski, 1983). Therefore, biomass of pearlside was estimated based on a Target Strength/Length relationship for a similar species of the same genus, Maurolicus muelleri (Sobradillo et al, 2019). Bluenose warehou (Hyperoglyphe antarctica), was selected as the likely species dominating a bentho-pelagic aggregation observed.…”
Section: Fish Biomass Estimationmentioning
confidence: 99%